rSNP_Guide-BASED EVALUATION OF SNPs IN PROMOTеRS OF THE HUMAN APC AND MLH1 GENES ASSOCIATED WITH COLON CANCER - D. A. Rasskazov; E. V. Antontseva; L. O. Bryzgalov; M. Yu. Matveeva; E. V. Kashina; P. M. Ponomarenko; G. V. Orlova; M. P. Ponomarenko; D. A. Afonnikov; T. I. Merkulova (Вавиловский журнал генетики и селекции)
Six regulatory SNPs (single nucleotide polymorphisms) of two human APC and MLH1 genes (rs75996864, rs76241113, rs78037487, rs80112297, rs80313086 and rs1800734) were evaluated by the previously developed rSNP_Guide method to compute the significance of the changes for binding of the SNP region with 40 transcription factors. For each SNP, all analyzed proteins were ranged according to the significance of the changes for protein binding to the alleles evaluated by Student’s t-test. We found that rs75996864, rs76241113, rs78037487, rs80112297, and rs80313086 of APC, as well as rs1800734 of MLH1 in humans concerned to the greatest extent the binding of transcription factors NF-Y, NFkB, c-Myb, RAR, YY-1, and Sp-1, which are known to be involved in colon cancer development. Our results substantiate investigation of associations of rs75996864, rs76241113, rs78037487, rs80112297, and rs80313086 in the APC gene with colon cancer by using commonly accepted medical and genetic protocols.